Effects of biomass on fuel gas production by gasification technology - Boontatao, Phanuwat; Hemathulin, Suwipong; Phuangbaidee, Sonlak (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The purpose of this research was to study the effects of biomass from sawdust and cassava rhizomes from fuel gas by gasification technology. The experiment started by preparing both types of biomasses to have the same size and drying them to reduce moisture under the same conditions. Subsequently, each type of biomass was used as fuel in a gasification fluidized bed reactor under a reaction temperature of 800 °C. To study the yield of products and the composition of fuel gas. The results showed that cassava rhizomes could produce fuel gas up to 83.7 wt%. In addition, cassava rhizomes can produce fuel gas with higher hydrogen and methane composition than sawdust. Therefore, this type of biomass should be further developed to be used as fuel gas for further energy benefits.